Olig1 function is required to repress Dlx1/2 and interneuron production in mammalian brain - Silbereis, John C. (2014)
Abnormal GABAergic interneuron density, and imbalance of excitatory versus inhibitory tone, is thought to result in epilepsy, neurodevelopmental disorders and psychiatric disease. Recent studies indicate that interneuron cortical density is determined primarily by the size of the precursor pool in the embryonic telencephalon. However, factors essential to regulate interneuron allocation from telencephalic multipotent precursors are poorly understood. Here we report that Olig1 represses production of GABAergic interneurons throughout the mouse brain. Olig1 deletion in mutant mice results in ectopic expression and upregulation of Dlx1/2 genes in the ventral medial ganglionic eminences and adjacent regions of the septum resulting in a ~30% increase in adult cortical interneuron numbers. We show that Olig1 directly represses the Dlx1/2 I12b intergenic enhancer and that Dlx1/2 functions genetically downstream of Olig1. These findings establish Olig1 as an essential repressor of Dlx1/2 and interneuron production in developing mammalian brain.